2022
DOI: 10.1097/pcc.0000000000002897
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children: Host Immunologic Responses

Abstract: Several weeks into the COVID-19 pandemic, a new syndrome causing sudden critical illness in children was identified (1)(2)(3)(4). Multisystem inflammatory syndrome in children (MIS-C), also called Pediatric Inflammatory Multisystem Syndrome Temporally associated with Severe acute respiratory syndrome coronavirus 2 (5), is a clinical syndrome of systemic inflammation, strongly associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, that has some similarities to, but is clinically and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Although genetic and immune system-related risk factors are thought to play a role in the pathogenesis of MIS-C, they have not been fully elucidated and the underlying etiology appears to be multifactorial. An autoimmune-mediated inflammatory process after infection, a cytokine storm initiated by a superantigen response, and a dysregulated immune response to exposure to SARS-CoV-2 viral antigens have been proposed as theories to explain its pathogenesis [ 11 , 12 ]. Immunological mechanisms, such as humoral and cellular adaptive immunity and innate response, play roles in the development of systemic inflammatory syndrome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genetic and immune system-related risk factors are thought to play a role in the pathogenesis of MIS-C, they have not been fully elucidated and the underlying etiology appears to be multifactorial. An autoimmune-mediated inflammatory process after infection, a cytokine storm initiated by a superantigen response, and a dysregulated immune response to exposure to SARS-CoV-2 viral antigens have been proposed as theories to explain its pathogenesis [ 11 , 12 ]. Immunological mechanisms, such as humoral and cellular adaptive immunity and innate response, play roles in the development of systemic inflammatory syndrome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An autoimmune-mediated inflammatory process after infection, a cytokine storm initiated by a superantigen response, and a dysregulated immune response to exposure to SARS-CoV-2 viral antigens have been proposed as theories to explain its pathogenesis [ 11 , 12 ]. Immunological mechanisms, such as humoral and cellular adaptive immunity and innate response, play roles in the development of systemic inflammatory syndrome [ 11 ]. Recent studies have also suggested that specific HLA haplotypes could be more frequently associated with the presence of this disease [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yonker et al have shown that weeks after acute infection, SARS-CoV-2 antigen can still be found in the gastrointestinal tract of patients who developed MIS-C [ 31 ]. Finally, similar to patients with toxic shock syndrome, a third theory suggests “superantigen-like activity of the SARS-CoV-2 spike protein” → incites a dysregulated immune response with cytokine storm [ 30 ]. As it pertains to cardiovascular dysfunction, the release of cytokines (TNF-⍺ IL-1β, IL-2, IL-6, and IFN-γ) is the known cause for left ventricular dysfunction, affecting both the extracellular matrix and myocyte contractility [ 32 ].…”
Section: Sars-cov-2 and Myocarditismentioning
confidence: 99%
“…Patients with MIS-C present several weeks after acute infection, have low viral load, low immunoglobulin M (IgM), and high IgG and IgA expression [29]. It is therefore plausible that like other viral triggers of autoimmunity, SARS-CoV-2 activates an autoimmune response resulting in tissue damage [20,30]. A second theory is that there is an uncontrolled immune response to prolonged presence of SARS-CoV-2 antigen.…”
Section: Covid-19 and Mis-cmentioning
confidence: 99%
“…[11; 12] Immunological mechanisms, such as humoral and cellular adaptive immunity and innate response, play roles in the development of systemic in ammatory syndrome. [11] Recent studies have also suggested that speci c HLA haplotypes could be more frequently associated with the presence of this disease. [13] It has been shown that infections, especially of the gastrointestinal and respiratory systems, have effects on microbiota composition.…”
Section: Introductionmentioning
confidence: 99%